2003
DOI: 10.1128/jcm.41.11.5212-5214.2003
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Focus and Kalon Enzyme-Linked Immunosorbent Assays for Antibodies to Herpes Simplex Virus Type 2 Glycoprotein G in Culture-Documented Cases of Genital Herpes

Abstract: Glycoprotein G-based herpes simplex virus type 2 (HSV-2) enzyme-linked immunosorbent assays from Focus and Kalon were performed with specimens from 118 patients with culture-documented genital herpes episodes, and their results were compared. Sensitivity was 52% by Kalon and 86% by Focus for first HSV-2 episodes and 100% (for each of the two tests) for recurrent HSV-2. Median times to seroconversion were 120 days by the Kalon assay, 21 days by the Focus assay, and 68 days by Western blotting assay. Values for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 7 publications
2
38
0
1
Order By: Relevance
“…Thirty-seven of the donors were HSV-2 seropositive. Infection with HSV-1 and HSV-2 was diagnosed by type-specific immunoblot (1) or glycoprotein G-based (15) immunoassays. HLA typing was performed by lowresolution PCR-based methods at Puget Sound Blood Center, Seattle, WA.…”
Section: Methodsmentioning
confidence: 99%
“…Thirty-seven of the donors were HSV-2 seropositive. Infection with HSV-1 and HSV-2 was diagnosed by type-specific immunoblot (1) or glycoprotein G-based (15) immunoassays. HLA typing was performed by lowresolution PCR-based methods at Puget Sound Blood Center, Seattle, WA.…”
Section: Methodsmentioning
confidence: 99%
“…Western blot testing is not commercially available, but several commercial assays are available which show high sensitivity and specificity in sexually active adults (154), but positive predictive value can still be diminished when used as a screening tool (155). Pending further studies and the availability of future prevention strategies such as vaccines, the utility, cost effectiveness and acceptability of routine screening of asymptomatic HSV infection in MSM attending GUM clinics remains to be determined.…”
Section: Herpes Simplex Virusmentioning
confidence: 99%
“…One study reported that the sensitivity of HerpeSelect increased for patients suffering from genital ulcer disease (GUD) compared to that for blood donors (6), perhaps because HerpeSelect may detect primary genital herpes earlier than the Kalon assay or even WB does (1,12).…”
mentioning
confidence: 99%